2018
DOI: 10.1158/0008-5472.can-17-3486
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analysis Predicts Causative Cis-Regulatory Mechanisms of the Breast Cancer–Associated Genetic Variant rs4415084

Abstract: Running title: Regulatory genomics of GWAS SNPsAbbreviations: GWAS -genome-wide association study; eQTL -expression quantitative trait loci; ASE -allele-specific expression; TF -transcription factor; LDlinkage disequilibrium; FPKM -fragments per kilobase of transcript per million mapped reads; LCASE -local chromosome allele-specific expression; DHS -DNase I hypersensitive sites; PWM -position weight matrix; TCGA -The Cancer Genome Atlas; ER+ -estrogen receptor positive; TAD -topologically associated domain; MA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…34 Furthermore, even if we find that a gene is dysregulated and suggest observed cis mutations as potentially causative, there may be multiple detected cis mutations and additional analysis is necessary to detect which of those are causing the change in ASE. 60 Nevertheless, because of the large number of noncoding mutations in cancer genomes, it is vital to have techniques for filtering out those mutations that are unlikely to be playing a regulatory role; indeed, we have found that the vast majority of noncoding mutations near genes do not appear to alter their expression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…34 Furthermore, even if we find that a gene is dysregulated and suggest observed cis mutations as potentially causative, there may be multiple detected cis mutations and additional analysis is necessary to detect which of those are causing the change in ASE. 60 Nevertheless, because of the large number of noncoding mutations in cancer genomes, it is vital to have techniques for filtering out those mutations that are unlikely to be playing a regulatory role; indeed, we have found that the vast majority of noncoding mutations near genes do not appear to alter their expression.…”
Section: Discussionmentioning
confidence: 91%
“…However, none of the individuals included in our dataset had a TERT promoter mutation or the previously described functional recurrent promoter mutations in breast cancer, such as the ones in the FOXA1 promoter. 15,17,20,60 This is not surprising due to the low levels of recurrence of even the most well studied noncoding somatic mutations. As a result, the overlap in predicted functional mutations by different methods is expected to be small, and further development of methods such as ours that are not based on recurrence is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Our direct comparisons between results (TF-drug associations) obtained with and without use of Delta-MOP scores (Table 1) are among the first direct statistical findings of the value of TFBS-SNP impact prediction for mechanistic studies of phenotypic variation, especially on genome-wide scales. More 'localized' applications, such as prioritization of a small number of candidate SNPs, are already being reported in the field (5). We also note that the basic methodology of our work can serve as a practical way to assess the value of new approaches to SNP scoring and prioritization, since the results of this methodology are testable findings at the TF and gene level (their roles in phenotype, as illustrated in Table 2 and Figure 4): there is more literature evidence to compare against at these levels than there is evidence for SNP function and mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A common approach is to find polymorphisms/variants that are statistically correlated with phenotypic differences, as in genome-wide association studies (GWAS) (1), familybased association tests (2), and expression quantitative trait loci (eQTLs) (3,4) for phenotype-related genes. However, statistically identified variants may not be functionally related to phenotypes (5), due to a variety of factors including linkage disequilibrium (LD). This problem is particularly pronounced in the case of non-coding variants, which represent the vast majority of GWAS findings (6,7) and often function by influencing gene regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation